Two stories with one happy ending. What constitutes the political culture differences between Egypt and Tunisia during and after the uprisings?. Issue 5 (4th July 2022) - Öney, Berna; Ardag, M. Murat
ABSTRACT: After the Arab uprisings, Egypt and Tunisia had divergent paths towards democratization. Can this outcome be attributed to differences in political culture orientations between Egyptians and Tunisians during and after the uprisings? By employing the Arab Barometer Waves II, III, and V data, this article analyses the associations among political culture orientations and depicts how these associations change over while accounting for the social, political, and economic peculiarities. To discover the relationships across indicators, we employ multiple techniques from the attitude network modelling framework: network trees, and Bayesian learning networks. Our results reveal the significantly different political culture orientations across the waves and countries and provide a comprehensive picture of how the paths of the two countries diverged over time. This study not only explains why Egyptian and Tunisian paths to democratization converged during the transition period and diverged in the aftermath but also introduces a novel empirical modelling strategy.